IMPLEMENTATION STEPPINGSTONES WITHIN SUSTAINABILITY ORIENTED MASTER STUDY PROGRAM FOR TEACHERS - Odina, Indra; Mikelsone, Ilze; Belousa, Inga; Grigule, Ligita (European Scientific Journal, ESJ, 2014)
The article is the outcome of the research into the national and European documents, regulations and normative acts and carried out analysis concerning context and rationale for creating and implementing an interdisciplinary and sustainability oriented master study program for teachers. By undertaking such a research, it is sought to identify and implement good practice in approaches to teaching and curriculum development; to find out how to embed sustainable development in institutional teaching and learning strategies; as well as assess the support required for widening and deepening this embedding process. The approach adopted throughout the research has been non-prescriptive, open and participatory. The article is an assessment of the current state of teacher education at master’s level in two universities of Latvia: the University of Latvia and Liepaja University, hence not a comprehensive review. Nevertheless it represents interdisciplinary and integrated research and its implementation in designing a sustainability oriented master study programme for teachers within in-service teacher education in Latvia.